CONCEPT OF MANAGEMENT SYSTEM PLATFORM MOBILE ROBOT BASED ON SERIAL TRACTOR «BELARUS 132» - M. M. Tatur (Системный анализ и прикладная информатика)
It is announced an innovative project to create a prototype multirobotic system. A distinctive feature of the project – the maximum use of components and software of domestic production. The mobile robot used the concept of multilevel management system, according to which the majority of workload is onboard computer. This will reduce the amount of data transmitted over a wireless link, and increase the efficiency of the development of algorithms for higherlevel control.